El realismo social, en la obra nuestro pan de Enrique Gil Gilbert - Rojas Valencia, Edinson Ramiro (2015)
For the present investigative work whose title: "THE SOCIAL REALISM, IN OUR WORK PAN DE ENRIQUE GIL GILBERT", he/she thought about as general objective, to conceptualize the social realism, in Our work Bread of Enrique Gil Gilbert, for that which the general methods were used as: the inductive, deductive, analytic, historical and the specific method for the literary analysis, the sociological of Efraín Subero; as technique, the bibliographical one that you/they allowed to fulfill all the activities proposed in the specific objectives in their group. The main result that was obtained of the sociological analysis is visualized the social features, economic, political and cultural elements. Also, the author locates us in the period of big changes for the Ecuador, in what refers to the power of the society that you/they stood out in that historical moment, of that which you concludes that the realism of Our Bread describes actions, characters and atmospheres of a real world where the author presides over the human drama, the incomprehension and social and ideological confrontation among liberal and conservatives; for what is recommended to educational and students, especially of the Career of Castilian Language and Literature of the National University of Loja, to develop the debate the debate of contents and the implicit and explicit messages of the literary works of Ecuadorian authors.